Sustainable Agriculture Growth Strategy to Ensure Food Security in Pakistan in Post-Pandemic Era - Tagar, Hamzo Khan; Barroso, Josué Gutiérrez (Archives of Business Research, 2022)
The study attempts to develop some coherent policy recommendations for growth sustainability to overcome the challenge of food insecurity for rapidly increasing populations with its changing consumption patterns and to address the 04th agricultural revolution of digital farming in a post-pandemic era in the greater public interest. The findings of part one of the study have been incorporated to assist in re-map the present strategic plan to promote the sustainable agriculture sector growth in the greater public interest to provide inputs i. e good quality seed, fertilizers, quality pesticides, modern tools and equipment, and easy credit services and feasible training to the farmers to re-build the cultivated areas for food security of rapidly increasing population and exports. The feasible policy recommendations are also helpful to make awareness at all regarding the significance of agriculture growth to cope-up the challenges and uncertainties and to make strategic collation between Private landowners and government agriculture sector concerns to reconcile the agriculture sector of the Indus valley for the benefit of the farmers to enhance their disposable income, food security for future generations and global welfare of the human in way of more food products at the lowest cost that will strengthen food supply chains.